2021
DOI: 10.3390/jcm10245733
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth and Small-for-Gestational Age Neonates among Prepregnancy Underweight Women: A Case-Controlled Study

Abstract: The aim of our study was to investigate whether prepregnancy underweight body mass index (BMI) is associated with preterm birth (PTB) and small-for-gestational age (SGA). This retrospective case-control study included 814 women with live singleton fetuses in vertex presentation that gave birth between January 2016 and November 2016 in two tertiary care hospitals. The study group (n = 407) comprised all women whose prepregnancy BMI was underweight (<18.5 kg/m2) and who delivered during the study period. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…With regard to the birth of SGA infants, maternal health conditions are of great importance for fetal growth. Several studies have revealed that the delivery of SGA neonates may be attributed to maternal pre-pregnancy underweight and some socioeconomic factors like poor education level [44,45]. The underlying mechanism of SGA may be related to placenta dysfunction and dyslipidemia [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the birth of SGA infants, maternal health conditions are of great importance for fetal growth. Several studies have revealed that the delivery of SGA neonates may be attributed to maternal pre-pregnancy underweight and some socioeconomic factors like poor education level [44,45]. The underlying mechanism of SGA may be related to placenta dysfunction and dyslipidemia [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition during pregnancy and low pre-pregnancy BMI have significant negative effects on birthweight [ 57 , 58 , 59 ]. Given that approximately 829 million people worldwide are exposed to hunger, this global problem may also have a deleterious effect on pregnant women in some regions and populations.…”
Section: Methodsmentioning
confidence: 99%
“…First, given the potential confounding bias, our study used a cohort of motherchild pairs with a one-and-a-half-year follow-up, and only women lacking undisputed high-risk factors for PTB were included in the study. Several studies used retrospective designs to investigate the association between GWG and PTB, which maybe a source of bias [25][26][27]. While most previous studies used statistical methods to correct for research bias caused by other high-risk factors of PTB, we excluded the PTB high-risk group from the beginning of the cohort study to accurately describe the relationship between GWG and PTB.…”
Section: Advantages and Limitationsmentioning
confidence: 99%